The Effect of ROA, DPR, EPS, and TATO on the Firm Value on Banking Companies Listed on BEI 2018-2020 Period - Muhammad Muhammad (Almana : Jurnal Manajemen dan Bisnis, 2022)
The company's long-term goal is to maximize the value of the company, price to book value (PBV) ratio is one of the financial ratios used to quantify company worth, and it is employed in this study to represent firm value. The goal of this research was to see how return on assets, dividend payout ratio, earnings per share, and total asset turnover affected the value of banking companies listed on the Indonesia Stock Exchange from 2018 to 2020. Purposive sampling was employed to gather a total sample of 10 samples over three years, resulting in a total of 30 data points in this study. Multiple linear regression analysis methods with a significant level of 5% are employed in the technical study of the data (0.05). The findings show that return on assets and earnings per share have a positive and considerable impact on the value of a company (price to book value). The dividend payment ratio and total asset turnover variables, on the other hand, have no bearing on the firm's value. The independent variable's ability to explain the link between the dependent and independent variables, namely the firm value of 0.814 or (81.4 %).